Low miR-214-5p Expression Correlates With Aggressive Subtypes of Pediatric ALCL With Non-Common Histology - Di Battista, Piero; Lovisa, Federica; Gaffo, Enrico; Gallingani, Ilaria; Damanti, Carlotta C.; Garbin, Anna; Ferrone, Lavinia; Carraro, Elisa; Pillon, Marta; Lo Nigro, Luca; Mura, Rossella; Pizzi, Marco; et al. (Frontiers in Oncology, 2021)
The unsatisfactory cure rate of relapsing ALK-positive Anaplastic Large-Cell Lymphoma (ALCL) of childhood calls for the identification of new prognostic markers. Here, the small RNA landscape of pediatric ALK-positive ALCL was defined by RNA sequencing. Overall, 121 miRNAs were significantly dysregulated in ALCL compared to non-neoplastic lymph nodes. The most up-regulated miRNA was miR-21-5p, while miR-19a-3p and miR-214-5p were reduced in ALCL. Characterization of miRNA expression in cases that relapsed after first line therapy disclosed a significant association between miR-214-5p down-regulation and aggressive non-common histology. Our results suggest that miR-214-5p level may help to refine the prognostic stratification of pediatric ALK-positive ALCL.